Electrospun Cellulose Nanofiber Membranes as Multifunctional Separators for High Energy and Stable Lithium-Sulfur Batteries. (21st March 2023) - Park, Dongjoo; Park, Sangbaek; Kim, Dong-Wan
Abstract : Although Li–S batteries (LSB) are one of the most promising electrochemical energy storage technologies, their practical applications are limited by their rapid capacity decay and uncontrolled lithium dendrite formation. In addition to the well-known role of a separator in lithium-ion batteries, LSB separators must perform additional functions. Using a facile electrospinning method, we developed an eco-friendly separator prepared from natural cellulose with an interconnected fibrous and porous structure rich in polar oxygen-containing functional groups. These polar functional groups enhance electrolyte wettability, polysulfide adsorption, and lithiophilicity, thus boosting LSB performance. A cellulose separator with a thickness (22 μ m) comparable to that of a commercial polypropylene (Celgard) separator delivers an initial discharge capacity of 1458 mAh·g −1 at 0.1C with a high sulfur utilization of 87%, including a high reversible discharge capacity of 1091 mAh·g −1 for 100 cycles, exhibiting a 1.8-times greater capacity retention than those of Celgard-containing LSBs. In addition, an excellent rate capability of 908 mAh·g −1 can be achieved at a high rate of 1C. These intriguing characteristics indicate that these separators could replace conventional synthetic polymer-based separators for commercial LSBs.